2006
DOI: 10.1590/s0004-282x2006000300028
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral SUNCT syndrome associated to chronic maxillary sinus disease

Abstract: -SUNCT syndrome (short lasting unilateral neuralgiform headache with conjuntival injection and tearing) is defined as short attacks of periorbital unilateral pain and accompanied by ipsilateral lacrimation and redness of the same eye. We present an unusual SUNCT case with bilateral pain that started five years ago after an acute maxillary sinus infection that evolved to chronic sinusitis. This association has been described in few SUNCT cases, but its causal role remains uncertain. The patient was a 58 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%
“…There have been cases of SUNCT syndrome resulting from craniosynostosis associated with seborrheic dermatitis 9 or intra‐orbital metastatic tumor 10 . A case of SUNCT syndrome associated with chronic sinusitis was recently reported, but atypical attacks with bilaterality and incomplete surgical response in terms of pain obscured the causal relationship between SUNCT syndrome and underlying sinusitis 11 . Another report of a case series of SUNCT syndrome suggested that the presence of sinusitis is likely to be an incidental finding in patients with SUNCT 12 .…”
Section: Discussionmentioning
confidence: 99%
“…While several symptomatic cases with intracranial lesions have been reported, 2‐8 SUNCT syndrome associated with extracranial lesions is very uncommon 9,10 . Although a few cases of SUNCT associated with sinusitis have been reported, 11,12 the relationship between sinusitis and SUNCT syndrome remains unclear. Here, we describe a case of symptomatic SUNCT syndrome caused by sinusitis, fulfilling the criteria of International Headache Society classification for SUNCT, which completely resolved after treatment of sinusitis.…”
mentioning
confidence: 99%
“…A number of the early articles on headache disorders were published by Farias da Silva and coworkers in the scientific journal Neurobiologia (Recife), which is one of the oldest journals in the area of neurology in Latin America, founded in 1943 by Ulysses Pernambucano. Another important journal containing articles on headache written by Brazilians is Arquivos de Neuropsiquiatria , which was founded in 1945 …”
Section: Publications In Headache Medicinementioning
confidence: 99%